Manajemen Penjaminan Mutu Dalam Meningkatkan Kedisiplinan Siswa Di MA Raudlatul Ulum Guyangan Pati - Aizzatin Aizzatin; Nur Uhbiyati; Musthofa Musthofa (Jawda: Journal of Islamic Education Management, 2021)
Improving student discipline is one way in quality assurance in Madrasah Aliyah Raudlatul Ulum Guyangan Pati. This study aims to : 1. Describe and analyze quality assurance planning in improving student discipline at MA Raudlatul Ulum Guyangan Pati 2. Describe and analyze the implementation of quality assurance in Madrasah Raudlatul Ulum Guyangan Pati 3. Describe and analyze the evaluation of quality assurance in Madrasah Aliyah Raudlatul Ulum Guyangan Pati.This research is qualitative research, which aims to understand a phenomenon that is happening observed by researchers. In the discussion of this thesis is used a method that is descriptive analysis that is the method aims to know how the Principal and his staff guarantee the quality of madrasah by improving the discipline of students in Madrasah Aliyah Raudlatul Ulum Guyangan Pati.In this research study that (1) Education quality assurance planning in improving discipline MA (2) Implementation of quality assurance discipline (3) Evaluation of quality assurance of education.From the results of the study, the author gave advice to educational institutions Raudlatul Ulum Guyangan Pati to maintain achievements that have not been achieved by madrasah, improve achievements that have not been achieved, cultivate a quality culture to advance madrasah, hold recruitment of teachers or educational personnel to succeed educational activities, and provide facilities or facilities and good learning infrastructure.